Last updated at March 9, 2017 by Teachoo

Transcript

Ex 4.1,1Prove the following by using the principle of mathematical induction for all n ∈ N: 1 + 3 + 32+……+ 3n – 1 = ((3𝑛 − 1))/2 Let P (n) : 1 + 3 + 32+……+ 3n – 1 = ((3𝑛 − 1))/2 For n = 1, L.H.S = 1 R.H.S = ((31 − 1))/2 = ((3 − 1))/2 = ((2))/2 = 1 L.H.S. = R.H.S ∴P(n) is true for n = 1 Assume that P(k) is true 1 + 3 + 32 +…..+ 3k – 1 = ((3𝑘 − 1))/2 We will prove that P(k + 1) is true. 1 + 3 + 32 +…..+ 3(k + 1) – 1 = ((3^(𝑘+1) − 1))/2 1 + 3 + 32 +…..3(k – 1) + 3(k) = ((3^(𝑘+1) − 1))/2 We have to prove P(k+1) from P(k) i.e. (2) from (1) From (1) 1 + 3 + 32 +…..+ 3k – 1 = ((3𝑘 − 1))/2 Adding 3k both sides 1 + 3 + 32 +…..+ 3k – 1 + 3k = ((3𝑘 − 1))/2 + 3k = ((3𝑘 − 1) + 2(3^𝑘 ))/2 = (3𝑘 − 1 + 2(3^𝑘 ))/2 = ( 3(3^𝑘 )− 1)/2 = (3^(𝑘+1) − 1)/2 Thus, 1 + 3 + 32 +…..3(k – 1) + 3(k) = ((3^(𝑘+1) − 1))/2 ∴ P(k+1) is true when P(k) is true ∴By the principle of mathematical induction, P(n) is true for n, where n is a natural number

Ex 4.1, 1
Important
You are here

Ex 4.1, 2

Ex 4.1, 3

Ex 4.1, 4

Ex 4.1, 5

Ex 4.1, 6

Ex 4.1, 7 Important

Ex 4.1, 8

Ex 4.1, 9

Ex 4.1, 10

Ex 4.1, 11 Important

Ex 4.1, 12

Ex 4.1, 13 Important

Ex 4.1, 14

Ex 4.1, 15

Ex 4.1, 16

Ex 4.1, 17

Ex 4.1, 18

Ex 4.1, 19

Ex 4.1, 20

Ex 4.1, 21 Important

Ex 4.1, 22

Ex 4.1, 23 Important

Ex 4.1, 24

About the Author

CA Maninder Singh

CA Maninder Singh is a Chartered Accountant for the past 8 years. He provides courses for Practical Accounts, Taxation and Efiling at teachoo.com .